“Откуда-то сверху мне дана уверенность, что мы переборем все трудности...” - Карленовна Епремян, Лилит (Musical Armenia, 2011)
PhD candidate, of Yerevan State Conservatory after Komitas Docent, Lilit Karlen Yepremyan writes the article "I intrinsically believe that we will overcome all difficulties". The article, published in the newspaper "Novoe Vremya" 31.02.2012, is an interview with a genius master, composer, pianist Alexander Haurtyunyan. World famous composer speaks about his thoughts, feelings and overcoming the problems, raised in the Armenian art.